Criteria expected of academicians in a local university. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
Recently, there has been much concern on the ranks of Malaysian universities in the Times Higher Education ranking exercise. It became clear that older and more established universities are slipping away from the top ranks. There is no doubt that the Ministry of Higher Education is trying very hard to avoid further decline and bring honour back to the local institutions of higher learning (IHLs). An outcome of their various continuous brainstorming sessions is the introduction of “National Higher Education Action Plan 2007-2010” (MoHE, 2007)